California Climate Change Center Report Series Number 2008-0XX - Miller, Norman L. (2008)
Para citar: N.L. Miller, P.B. Duffy, D.R. Cayan, H. Hidalgo, J. Jin, H. Kanamaru, M. Kanamitsu, T. O’Brien, N.J. Schlegel, L.C. Sloan, M.A. Snyder, K. Yoshimura 2008. An Evaluation of Simulated California Climate Using Multiple Dynamical and Statistical Downscaling Techniques. The California Energy Commission, PIER Energy-Related Environmental Research Program. CEC-500-2008-XXX.